LEAVING THE PUBLIC CAPITAL MARKET: A LITERATURE SURVEY ABOUT THE GOING PRIVATE DECISION - Ehn, Lucia (European Scientific Journal, ESJ, 2015)
The going private decision is less examined in the corporate finance literature compared to the IPO topic, although it is of similar importance in a company’s life. This paper surveys previous theoretical and empirical studies discussing the going private decision. Deeper insights are provided about reasons which motivate companies to leave the public capital market. The role of regulatory changes like the passage of Sarbanes-Oxley Act in 2002 and their implications for the decision making process of US listed companies concerning staying public or going private are addressed. A literature synopsis is provided about different aspects within the delisting topic. Literature about abnormal returns during the announcement of a going private transaction, bid premiums paid to investors as well as characteristics of companies which typically decide for privacy is reviewed. The current stage of research is analyzed in order to develop further relevant exploration areas within the going private topic. This paper also explains investors’ incentives. A precise recognition of potential going private companies on the public capital market allows shareholders to collect not only abnormal returns, but also bid premiums and enable them to increase their earnings within a short period of time. Additionally, also companies profit from knowledge about going privates. Being aware of the large costs, they can avoid unnecessary expenses of their public-to-private-and-back cycles.